Os consórcios de produtores rurais no complexo agroindustrial citrícola paulista: das gatoperativas aos gatosórcios- a velha forma de contratação de mão-de-obra rural - Barbosa, Gabriela da Rocha (Universidade Federal de São Carlos, 2008)
Since the 90 s, following the world productive restructuring trend, the industries of concentrate orange juice from the citrus agribusiness complex in São Paulo state refuse to be responsible for hiring people to work in the orange crop and, in this manner, new forms of recruiting workers are arising. Thus, the present work is intended for verifying if a new class of hiring named Rural Producers Partnership serves its purpose of directly hire orange pickers thus guaranteeing the formalization of the job as well as serving all work legislation required by the formalization. The partnerships were created as an alternative to rural work co-ops whose activities were interrupted by the Brazilian Department of Labor in 1999. The "gatoperativas ", as they were known, promoted a growing instability in rural work conditions when depriving workers from their major achievements, that is, their direct labor contract and labor rights. Since these activities were repressed, the partnerships have been a solution to the end of the intermediary manpower promoted by the recruitment agents. In this work it is also concluded that the partnerships are dominated by these agents, and their work relations are not organized by the producers, thus jeopardizing the work activity.
Keywords: Complexos agroindustriais; Trabalhadores rurais; ENGENHARIAS::ENGENHARIA DE PRODUCAO